If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(s + -4) + 13 = 0 Reorder the terms: 7(-4 + s) + 13 = 0 (-4 * 7 + s * 7) + 13 = 0 (-28 + 7s) + 13 = 0 Reorder the terms: -28 + 13 + 7s = 0 Combine like terms: -28 + 13 = -15 -15 + 7s = 0 Solving -15 + 7s = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 7s = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 7s = 0 + 15 7s = 0 + 15 Combine like terms: 0 + 15 = 15 7s = 15 Divide each side by '7'. s = 2.142857143 Simplifying s = 2.142857143
| .47=log(x) | | 0.11x=56 | | 5-x=8-x-3 | | 4x-17=4x | | 16=4(1+7x)-8(3x-5) | | f=6/5(n-18) | | 8-3(2x+3)=11 | | 4x-5=4x+12 | | -3(2x+3)=11 | | g=5/3(p-49) | | 4-5-13-18+2= | | 14=8x+7-x | | 458000*9= | | ln(x-4)=6 | | 90=2(7x+3) | | 3x+5x-8+4-11+17x-42+7x=-6 | | -252=-7(-6x+6) | | -91=-7(3r+4) | | 8w-14=434 | | 3(-5x+2)=-84 | | 6x+27=36 | | 7x+9y=103 | | 2x^2+-2x^2= | | (5y+3)(1+y)=0 | | (x-3)-2=6-2(x-1) | | -126=-3(-6-8n) | | -18-3p=-(p+4) | | 9y^3-11x^2+2-13y^3-15x^2= | | 2b+3b-4b+3=17 | | 10y^3-11x^2+2-12y^3-13x^2= | | -82=-2(6-5r) | | 18y^2-18x^3+2-18y^4-18x^5= |